2019
DOI: 10.1016/j.jaim.2018.02.137
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the effects of Ayurvedic massage in post-stroke patients

Abstract: Background Few stroke patients have reported improvements after Ayurvedic massage. Unfortunately, there is a dearth of indexed literature to support the use of this in rehabilitation. Objectives To objectively measure the differences between patients with stroke who received Ayurvedic massage in addition to standard Physiotherapy (PT) versus those who received only standard PT. Materials and methods The study was a prospective case control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…There were limited studies on the subtypes of manual therapeutic massage used during the acute phase of ischemic stroke. Sankaran et al found that when Ayurvedic massage was administered to patients one-month post-stroke who exhibited flaccidity, it expedited their ability to stand with minimal support and reduced the requirement for antispastic medications upon discharge [ 21 ]. As stated in the introduction, prior research on TTM's use in stroke treatment has predominantly focused on the subacute to chronic stages.…”
Section: Discussionmentioning
confidence: 99%
“…There were limited studies on the subtypes of manual therapeutic massage used during the acute phase of ischemic stroke. Sankaran et al found that when Ayurvedic massage was administered to patients one-month post-stroke who exhibited flaccidity, it expedited their ability to stand with minimal support and reduced the requirement for antispastic medications upon discharge [ 21 ]. As stated in the introduction, prior research on TTM's use in stroke treatment has predominantly focused on the subacute to chronic stages.…”
Section: Discussionmentioning
confidence: 99%
“…5 ) ( Table 2 , Table 3 ) improves local blood flow, reduces inflammation, pain, muscle spasm and hastens the healing process [ 29 ]. Abhyanga [ 30 ] (massage) followed with Shastika shali pinda sweda (bolus fomentation of boiled rice grains tied in piece of cloth) helps in relieving muscle stiffness, heaviness and improves muscle strength [ 30 , 31 ]. Rhythmically applied pressure using hands in a systematic fashion helps in mechanical stimulation of the soft tissues, thus improving range of motion, relaxation of muscles and reduce pain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For good measure, 54.5 % of respondents agree and 40.9 % of respondents disagree on Ayurvedic treatment can treat the specific conditions of stroke. Furthermore, a study conducted by Harini, et al (2019) prioritizes; the safety profiles of classical Ayurveda and conservative western biomedicine in Acute Ischemic stroke are similar and utilization of Ayurveda massage in post stroke patients with flaccidity promotes faster standing with minimal support including assistance and lead to less need for antispastic drugs at discharge (Sankaran, Kamath, Nambiar, & Kumard, 2019). Hence, respondents has provided the data according to their intellectual level.…”
Section: Data Presentation and Analysismentioning
confidence: 99%